Creol Potuguese of the Tugu Village: Colonial Heritage in Jakarta Based on the Historical and Linguistic Review - Suratminto, Lilie (TAWARIKH, 2011)
ABSTRACT: In 1641, the Dutch seized Malacca from Portuguese hands. The Portuguese society, which is left now, occupied the territory of âKampungâ (Village) of Portuguese on the west coast of Malacca. VOC (Vereenigde Oost Indische Compagnie) has then brought some of them to Batavia to be employed as unskilled laborers and soldiers. At Batavia (now Jakarta), they were forced to convert to Protestantism and the service was held at the Portuguese church outside of the city walls. To defend from attacks of Bantam Sultanate, some of them were placed in Tugu Village, outside of Batavia (now North Jakarta). They form an exclusive community by maintaining the Portuguese Creole language. This paper discusses the historical and linguistics of the Potuguese Creole by a small portion of the population, especially by older generations which were decreased naturally. They had to master the Indonesian language very well since the children entered the Elementary School. From the data contained inscriptions on the tombstone monument next to the church, seen their family names, for example Quiko, Abrahams, Michiels, Andries, Browne, Salomons, and others seem Portuguese influence. KEY WORD: Portuguese Creole language, Tugu Village, extinction of languages, and historical and linguistic approachs.About the Author: Dr. Lilie Suratminto is a Senior Lecturer at the Dutch Study Program, Faculty of Humanities UI (University of Indonesia), UI Campus Depok 16424, West Java, Indonesia. He can be reached at: masliliek@yahoo.comHow to cite this article? Suratminto, Lilie. (2011). âCreol Potuguese of the Tugu Village: Colonial Heritage in Jakarta Based on the Historical and Linguistic Reviewâ in TAWARIKH: International Journal for Historical Studies, Vol.3(1) October, pp.1-30. Bandung, Indonesia: ASPENSI [Asosiasi Sarjana Pendidikan Sejarah Indonesia] and UVRI [Universitas Veteran Republik Indonesia], ISSN 2085-0980. Chronicle of the article: Accepted (August 17, 2011); Revised (September 19, 2011); and Published (October 28, 2011).